Behind the Instagram post: unpacking ideological framing in @Folkative coverage of Indonesian political controversies - Azzahra Nabila Azhari; Mohamad Ikhwan Rosyidi (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This research examines how @Folkative, one of Indonesia’s most influential Instagram-based information platforms, frames political controversies through ideological language. By applying Fairclough’s three-dimensional model of critical discourse analysis, the research focuses on two viral posts: the Pertamina corruption case and the TNI Bill. The findings reveal that @Folkative employs strategic lexical choices, a visual and informal tone, and bilingualism as a powerful ideological framing tool to shape audiences’ perceptions of political events in Indonesia. The study also shows how @Folkative transforms passive media use into active discussion, where followers engage in comments, sarcasm, and debate over political issues. This research highlights how digital platforms, such as @Folkative, influence political narratives and public opinion in Indonesia’s evolving media landscape, particularly among young people.